Asuhan Keperawatan pada Lansia dengan Gouth Arthritis dan Hiperkolesterolemia (IJM: Journal of Multidisiplinary, 2025)
Gout arthritis is a joint inflammation caused by the accumulation of uric acid crystals, while hypercholesterolemia is a condition characterized by increased cholesterol levels in the blood, which can trigger cardiovascular diseases. This study employed a case study method with a family nursing care approach, encompassing the stages of assessment, nursing diagnosis, planning, implementation, and evaluation. The purpose of this study was to apply nursing care to elderly patients with gout arthritis and hypercholesterolemia in Peunayong Village, Kuta Alam District, Banda Aceh City. The results showed a significant reduction in joint pain intensity, improved patient and family knowledge regarding the diseases, better regulation of a low-purine and low-fat diet, and enhanced patient ability in performing self-care and controlling risk factors continuously. The implementation of comprehensive, educational, and continuous nursing care had a positive impact on improving the quality of life of elderly patients with gout arthritis and hypercholesterolemia, particularly through non-pharmacological therapy and family empowerment approaches.